Legal Protection for Nature Reserves As Providers Of Watering Needs For Food Security - Anwar, Jarkasi; Muslih, Muhamad (Unram Law Review, 2024)
The growth of online buying and selling transactions in the business world in Indonesia needs legal protection for the parties. Legal protection issues in the e-commerce sector, include issues regarding the rights of parties, especially consumers of buying and selling online. This research aims to determine the extent to which online transactions for buying and selling are protected by consumer law and the legal efforts that consumers can take if there is fraud in online transaction. The research method used in this Article is a normative juridical research method. This research is qualitative descriptive. Data used in this research is secondary data which covers Primary, secondary, and tertiary laws. Data collection is a library technique. Qualitative description is used as a data analysis technique. The findings of this research and discussion determine that the legal protection for consumer in an online transaction is provided in Law Number 19 of 2016 concerning Information and Electronic Law and Law Number 8 of 1999 concerning the Protection of Consumers. The protection for consumers is supported by the involvement of various government agencies, national consumer protection agencies, and non-government consumer protection agencies. Conflicts related to non-fulfillment of obligations can be resolved using litigation and non-litigation lawsuits.